Stigmatizing Attitudes Towards Mental Disorders Among Non-Mental Health Professionals in Six General Hospitals in Hunan Province - Qiuxia Wu; Qiuxia Wu; Qiuxia Wu; Qiuxia Wu; Qiuxia Wu; Qiuxia Wu; Xiaoyang Luo; Shubao Chen; Shubao Chen; Shubao Chen; Shubao Chen; Shubao Chen; et al. (Frontiers in Psychiatry, 2020)
Background: There have been few studies on the stigma associated with mental disorders among non-mental health professionals in general hospitals in China. This study seeks to explore mental health-related stigma and the desire for social distance among non-mental health professionals in general hospitals in Hunan Province in China.Methods: The study was carried out with 1123 non-mental health professionals in six general hospitals in Hunan Province by using a questionnaire with a case vignette describing either schizophrenia, depression, or generalized anxiety disorder (GAD). Questions were asked about the attitudes of participants and other people towards individuals with mental disorders and the willingness to come into contact with them.Results: The people described in the vignette were considered dangerous by 84.4% of participants for schizophrenia, 72.0% of participants for depression, and 63.1% of participants for GAD. Besides being dangerous, people with schizophrenia were perceived as unpredictable and as the least suitable for voting for as a politician or employing. Around 50% of participants believed the problems described in the vignette were due to personal weakness. Over 70% of the non-mental health professionals were not willing to have the people described in the vignette marry into their family. The participants had gained their mental health-related knowledge mainly through the media, mostly from newspapers.Conclusions: The current study found a significant stigma towards individuals with mental disorders and a desire for social distance from such people among non-mental health professionals in general hospitals in Hunan Province. Anti-stigma interventions should focus on addressing non-mental health professionals' beliefs on dangerousness and unpredictability.